Is Body Mass Index for-age Related with Dental Caries in Children? - Esra Kızılcı; Cansu Demiroğlu; Burcu Duman; Büşra Ayhan (Journal of Pediatric Research, 2022)

(untitled)
Aim:Nutrition has a significant impact on dental health. The aim of this study was to investigate the relationship between dental caries and body mass index (BMI)-for-age.Materials and Methods:Four hundred and fifty-one children who were 5-14 years were included in this study. The children were examined according to dmft/DMFT indexes with mirror - sound and panoramic radiography. After taking weight and height measurements, the BMI-for- age calculation, age, weight and height status were entered into the World Health Organization AnthroPlus Software program in order to obtain a z-score for each child. The children were grouped according to their z-scores as Group 1: normal; Group 2: overweight; Group 3: fat/obese; Group 4: underweight; and Group 5: severely underweight. Data were analyzed using SPSS software 22, correlation, frequency and independent sample t-tests.Results:The mean age of the children was 9.1±2.5 years. The mean DMFT/dmft values were 6.97±3.79. 55% of the children were of normal weight, 16.2% were overweight, 11.8% were fat/obese, 12.2% were underweight and 4.8% were severely underweight. In terms of DMFT/dmft, when the groups were compared, a statistically significant difference was found between Group 3 and Groups 1, 4 and 5 (p<0.05).Conclusion:The risk of caries increased as the weight increased in the children participating in this study. Obesity can be considered as an important risk factor for dental health. Informing parents about children’s poor eating habits can have an impact on dental health.